Breaking the mold: designing sequential sight singing and aural skill lessons for various learning styles - Bryson, Sarah (Kansas State University, 2022)
These three lessons are designed solidify confidence with specific intervals and patterns used frequently in the annual University Interscholastic League Concert and Sight-Reading Evaluation by appealing to visual, aural, and kinesthetic learners. By teaching sight-reading away from the typical format and using creative approaches every singer in the classroom, no matter their learning style, will grow as a musically literate student. Each of these lessons utilize different materials and are designed to feel like activities instead of mundane work, while giving the director invaluable informal and formal feedback about the students’ progress as an ensemble and as individuals. These are sequential lessons that can be built upon the entire school year and are inclusive for students of varying ability levels. My experience with the Kansas State University School of Music has inspired me to broaden my educational horizons and see past the “Texas way” of thinking and teaching. All too often as educators we get stuck in our own standard practices instead of seeking out new ideas, and this program inspired me to be a lifelong learner and constantly look for new ways of doing things instead of doing what is comfortable. By connecting with educators across the country I have gained new ideas and perspectives that have been incredibly helpful in my career, as well as insightful lectures from the faculty I have worked with. My time at K-State has coincided with finding my stride as a choral educator, and I am grateful for this program guiding and shaping me as an innovative director.
Keywords: Choir; Middle school; Learning styles; Aural skills